Does customer service quality influence customer decision making process to use bank plan savings product? a study at Bank Mandiri Cirebon Siliwangi Branch - Suwandi Suwandi; Jennifer Sujono; Wawat Hermawati (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2022)
Purpose — To determine the effect of customer service quality on customer decision to use bank plan savings of Bank Mandiri Cirebon Siliwangi branch.Research method — This study used a quantitative approach with a simple linear regression analysis technique. The research data is processed by statistical software. Samples in this study were 91 respondents with probability sampling using a simple random sample technique.Result — The findings indicated that customer service quality has a significant influence to customer decision in using bank plan savings of Bank Mandiri Cirebon Siliwangi Branch. In addition, this study also discovered that customer service quality has a contribution of 27.8% to the customer's decision to use the bank product, while the remaining 72.7% is influenced by other factors which is not examined by the author.